2014
DOI: 10.1123/ijspp.2013-0385
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiological Response to Aerobic Short-Interval Training in Trained Runners

Abstract: The results showed that AESIT with 10-s work phases alternating with 20 s of passive rest and a running speed close to vVO(2max) gave a systemic aerobic metabolic profile similar to slow continuous runs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…This indicated that strictly planning interval-type exercise respecting all variables allows the regulation and the predictability of the acute physiological responses (Tschakert et al, 2015). In a recent paper we could show that even with a high-intensity running speed, short 10 s intervals, 20 s passive recovery but a very low mean load below LTP 1 , lactate levels were only slightly higher than resting level, and 30 min of exercise was clearly below the maximal duration which was, however, not obtained in this study (Wallner et al, 2014). …”
Section: Prescription Of Intensitycontrasting
confidence: 64%
“…This indicated that strictly planning interval-type exercise respecting all variables allows the regulation and the predictability of the acute physiological responses (Tschakert et al, 2015). In a recent paper we could show that even with a high-intensity running speed, short 10 s intervals, 20 s passive recovery but a very low mean load below LTP 1 , lactate levels were only slightly higher than resting level, and 30 min of exercise was clearly below the maximal duration which was, however, not obtained in this study (Wallner et al, 2014). …”
Section: Prescription Of Intensitycontrasting
confidence: 64%
“…Nevertheless, other studies are warranted to verify the chronic effects of low volume HIIE on other parameters to confirm its utility. However, as shown by Wallner et al (2013) even high intensity intervals at vVO 2max may lead to rather low lactate responses in case the overall mean load is low and the duration of the strenuous interval bouts is short showing the need for further studies systematically varying the variables of interval exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, increases in running speed lead to greater levels of neuromuscular engagement (mainly in the hamstring muscles) 19 . Likewise, some differences have been observed between HIIT protocols (with different durations of work and relief intervals) in both physiological and neuromuscular impact 20, 21, 22, 23, 24, 25, 26. Coaches must themselves decide how to manage HIIT inclusion in running plans for endurance athletes, so knowledge about the acute changes induced by HIIT protocols and the long-term adaptations induced by HIIT-based interventions in endurance runners plays a key role in the training prescription.…”
Section: Introductionmentioning
confidence: 99%